Omentin attenuates atherosclerotic lesion formation in apolipoprotein E-deficient mice. Issue 1 (28th December 2015) - Hiramatsu-Ito, Mizuho; Shibata, Rei; Ohashi, Koji; Uemura, Yusuke; Kanemura, Noriyoshi; Kambara, Takahiro; Enomoto, Takashi; Yuasa, Daisuke; Matsuo, Kazuhiro; Ito, Masanori; Hayakawa, Satoko; Ogawa, Hayato; et al.
Abstract: Aims: Obesity is associated with the development of atherosclerosis. We previously demonstrated that omentin is a circulating adipokine that is downregulated in association with atherosclerotic diseases. Here, we examined the impact of omentin on the development of atherosclerosis with gain-of-function genetic manipulations and dissected its potential mechanism. Methods and results: Apolipoprotein E-deficient (apoE-KO) mice were crossed with transgenic mice expressing the human omentin gene (OMT-Tg) mice in fat tissue to generate apoE-KO/OMT-Tg mice. ApoE-KO/OMT-Tg mice exhibited a significant reduction of the atherosclerotic areas in aortic sinus, compared with apoE-KO mice despite similar lipid levels. ApoE-KO/OMT-Tg mice also displayed significant decreases in macrophage accumulation and mRNA expression of proinflammatory mediators including tumour necrosis factor-α, interleukin-6, and monocyte chemotactic protein-1 in aorta when compared with apoE-KO mice. Treatment of human monocyte-derived macrophages with a physiological concentration of human omentin protein led to reduction of lipid droplets and cholesteryl ester content. Treatment with human omentin protein also reduced lipopolysaccharide-induced expression of proinflammatory genes in human macrophages. Treatment of human macrophages with omentin promoted the phosphorylation of Akt. Inhibition of Akt signalling abolished the anti-inflammatory actions of omentin in macrophages. Conclusion: These data document for the first time that omentin reduces the development of atherosclerosis by reducing inflammatory response of macrophages through the Akt-dependent mechanisms.